Bioclimatic Modeling of Current Geographic Distribution and Future Range Shifts of Selected Edible Mushrooms in Nigeria - Tiamiyu, Bashir Bolaji; Lateef, Azeez Adebola; Ajadi, Ibrahim; Adeyemi, Sherif Babatunde; Owolabi, Patience Olatayo; Sagaya, AbdulQuadri; AbdulSalam, Mustapha; AbdulKareem, Khadija AbdulHamid; Mustapha, Oba Toyin (Sahel Journal of Life Sciences FUDMA, 2024)
Mushrooms, as part of the fungal kingdom, are essential components in nutrient cycling and carbon retention in terrestrial ecosystems. Monitoring the impact of climate change on fungi in their natural habitat is difficult because most species reside below the soil surface. As a result of few reported occurrence records in Nigeria, we model the species distribution of two edible mushrooms, namely, Pleurotus ostreatus and Macrolepiota procera, using MaxEnt to predict the potential future range shifts under different climate change scenarios. In this study, we have calculated high model performances based on the Area Under Curve (AUC) values generated (0.778-0.873). In the modeling approach, the two species were predicted to have an expansion of their localized fundamental niches, pointing to the influence of precipitation as an important macroclimatic predictor. Highly suitable habitats for the two species were discovered primarily in Southern Nigeria, with less habitat suitability in the Northcentral zone in 2050. The predicted models in this study do not tell missing geographical information, which could be achieved through citizen science for occurrence records and biodiversity conservation. However, they may be used to explore potentialities, such as understanding the possible distribution patterns of the two mushroom species in Nigeria. This can serve as a useful baseline to enhance the utilization and conservation efforts of these macrofungi as a result of climate change, habitat loss, and rapid urbanization.